G183(P) Learning together study days: cross specialty education to improve children and young people's health. (27th April 2015) - James, DR; Race, H; Sen, C; Fawbert, K
Abstract : Aims: The UK is lagging behind the majority of Europe in children and young people's health outcomes. 1 One possible hypothesis for this is the lack of integration between primary, secondary and tertiary care. The World Health Organisation supports effective inter-professional education as it enables effective and collaborative practice. 2 There is published evidence that inter-professional learning can lead to better patient care and safety, reduced mortality rates and better use of specialist health resources. 3–5 Methods: Following focus group work and a pilot study day, the authors created three study days: Child and Adolescent Mental Health, Public Health and Adolescent Sexual Health. These are areas where good care crosses traditional medical specialties and health care professions. Royal College curricula were analysed to define learning outcomes. The study days were advertised to paediatric, GP and relevent specialty trainees as well as other children's and young people's health professionals. Each day featured a mix of lecture and small group case based learning. Results: The three days were attended by 163 trainees (85 paediatric, 52 GP, 26 other). We received pre and post course online feedback from 85 (53%) and 104 (64%) trainees respectively. Across the three days the proportion of delegates who strongly agreed with the statement 'My learning is enhanced when I learn with health care professionals from different specialties' increased from 40.7 to 60.2% (Tables 1 and 2 ). Conclusions: This series demonstrates that it is both desirable and feasible to offer cross specialty inter-professional education in Children and Young People's health and that it not only increases confidence and knowledge in the individual subject areas but also improves the delegates' own perceptions of learning in the wider cross specialty team. References: Wolfe I, Thompson M, Gill P, et al . Health services for children in Western Europe. Lancet 2013;381 (9873):1224–1234 WHO Framework for Action on Interprofessional Education Collaborative Practice 2010 Simmonds S, Coid J, Joseph P, et al . Community mental health team management in severe mental illness: a systematic review. Br J Psychiatry 2001;178 :497–502 Naylor CJ, Griffiths RD, Fernandez RS. Does a multidisciplinary total parenteral nutrition team improve outcomes? A systematic review. J Parenter Enteral Nutr . 2004;28 :251–258 Holland R, Battersby J, Harvey I, et al . Systematic review of multidisciplinary interventions in heart failure. Heart 2005;91 :899–906